MODEL DIAGRAM JANECKE KESETIMBANGAN FASA PADAT-CAIR PROSES TIPE SOLVAY UNTUK PEMBUATAN Na2CO3 DAN KCI DARI ABU SABUT KELAPA - Wahyuningsih Wahyuningsih (Universitas Diponegoro, 2012)
Abstract Sodium carbonate and Kalium Chlorde are two major Chemical compound in industry such is glass, pulp, soap and paper industry. Sodium carbonate and kalium chloride can be produces simultaneously from coconut shell fiber as by solvay type process. The ash coconut shell fiber contain larger portion of Kalium carbonate (35-45%-b Dikaliumoxide). The Material used in the research were kalium carbonate , kalium bicarbonate sadium chloride, carbon dioxide , kalium chloride, sodium carbonate ,sodium bicarbonate and water. The research parameter were the solubility of the salts kalium carbonate sodium chloride, sodium carbonate ,kalium chloride, sodium bicarbonate and kalium bicarbonate. For the solid liquid phase equilibrium data the observation for K+-Nα+- CI- CO3 - -H2O system was conducted. 30-40C and for K+-Nα+- CI- HCO3 - -H2O system the observasion was conducted at 55-65C They also help to identify the separation boundaries , the condition of operation ,the lise of solids that are most likely to precipitate and many more. Information, the generated SLE-phase ,diagrams such as phase boundary data and saturation point data may be used to solve grapichally the mass balance equations is related to the operational pathson the phase diagrams, the temperature dependent phase boundaries and the solubility index it is possible to simultaneously design.analize and simulate both continous flow sheets wich crystallization operation and sequences of batch.operations. The Simultaneous graphical not only provides a visualization of the process operation, but also,provides very goods initial estimates for future simulations with rigorous model.Jancke diagram .from Na + K t – CI- HCO3 - -H2O system at 50 C has the crystallization field.while the widest crystallization field for the Na + K t – CI- HCO3 - -H2O system was obtained from process at 400C Keyword : Janecke diagram; proses solvey